Characterizing correlations among disease severity measures in osteochondral tissues from osteoarthritic knees. Issue 5 (27th July 2020) - Werner, Nicole C.; Stoker, Aaron M.; Bozynski, Chantelle C.; Keeney, James A.; Cook, James L.
Abstract: Osteoarthritis (OA) is a complex disease with biologic, biomechanical, and clinical heterogeneity among patients. Relationships among OA tissue metabolism, histopathology, and extracellular matrix (ECM) composition have not been well characterized. It was hypothesized that moderate ( r = .4‐.69) to strong ( r > .7) correlations exist among these different measures of disease severity in osteochondral tissues from OA knees. Joint surfaces were obtained from patients (n = 6) undergoing total knee arthroplasty. Osteochondral explants (n = 136) were created and cultured for 3 days. Culture media were collected for biomarker analyses, and tissue was assessed for viability, histological scoring, and ECM composition. Correlations among media biomarker concentrations, histological scoring, ECM composition, and viability were determined using a Spearman correlation. GRO‐α, IL‐6, IL‐8, and MCP‐1 showed strong positive correlations to each other, and moderate positive correlations to NO, PGE2, and MMP‐2. Total MMP activity, MMP‐9, and MMP‐13 had strong positive correlations to each other, and moderate positive correlations to MMP‐1. MMP‐2 had a moderate to strong positive correlations to histological scores (total and cartilage structure) and collagen content. MMP‐2, IL‐6, IL‐8, and MCP‐1 had moderate negative correlations, and MMP‐9 had a moderate positive correlation, to viability. GRO‐α, IL‐6, IL‐8, and MCP‐1 had moderate positive correlations to collagen content. MMP‐9, MMP‐13, and total MMP activity had moderate negative correlations to tissue GAG. The data suggest links among proinflammatory and degradative pathways are present in OA osteochondral tissues. Further characterization of these links have the potential to delineate mechanisms of disease and diagnostic and therapeutic targets for knee OA.